Development of ecological and economic measures for creating of the sustainable land use - Hetmanchyk, I.; Kolhanova, I. (Land Management, Cadastre and Land Monitoring, 2017)
The article deals with ecological and economic measures for creating of the sustainableland use, it’s current state and problems as well as areas of improvement.These measures directed to ensure balanced of needs of the population and economicsectors by land resources, rational use and protection of lands, preservationof landscape and biological diversity, creation of environmentally safe living conditionsof the population and economic activity and protection of lands from depletion,degradation and pollution.Key words: sustainable land use, lands of nature conservation and natural reservepurpose, ecological network, agrolandscape.